2016
DOI: 10.1073/pnas.1616294113
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the LCIB protein family reveals a new group of β-carbonic anhydrases

Abstract: Aquatic microalgae have evolved diverse CO 2 -concentrating mechanisms (CCMs) to saturate the carboxylase with its substrate, to compensate for the slow kinetics and competing oxygenation reaction of the key photosynthetic CO 2 -fixing enzyme rubisco. The limiting CO 2 -inducible B protein (LCIB) is known to be essential for CCM function in Chlamydomonas reinhardtii. To assign a function to this previously uncharacterized protein family, we purified and characterized a phylogenetically diverse set of LCIB homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 46 publications
1
62
0
Order By: Relevance
“…The pyrenoid matrix contains the Rubisco holoenzyme (RBCS/RbcL); its chaperone Rubisco activase (RCA1); essential pyrenoid component 1 (EPYC1), a Rubisco linker protein important for Rubisco packaging in the pyrenoid (Mackinder et al, 2016); and a protein of unknown function (Cre06.g259100; Kobayashi et al, 2016). Under very low CO 2 conditions, the LCIB/LCIC complex, whose role is still uncertain (Jin et al, 2016), is known to form puncta around the pyrenoid periphery (Yamano et al, 2010). Recently, a Ca 2+ -binding protein, CAS, has been shown to specifically localize to the pyrenoid tubules at low CO 2 (Wang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pyrenoid matrix contains the Rubisco holoenzyme (RBCS/RbcL); its chaperone Rubisco activase (RCA1); essential pyrenoid component 1 (EPYC1), a Rubisco linker protein important for Rubisco packaging in the pyrenoid (Mackinder et al, 2016); and a protein of unknown function (Cre06.g259100; Kobayashi et al, 2016). Under very low CO 2 conditions, the LCIB/LCIC complex, whose role is still uncertain (Jin et al, 2016), is known to form puncta around the pyrenoid periphery (Yamano et al, 2010). Recently, a Ca 2+ -binding protein, CAS, has been shown to specifically localize to the pyrenoid tubules at low CO 2 (Wang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A role in the conversion of CO 2 to HCO 3 − is likely, as several homologs of LCIB were recently shown to be functional β-carbonic anhydrases. However, recombinant LCIB/C had no carbonic anhydrase function (Jin et al, 2016), suggesting that the complex may be tightly regulated or may require additional factors for proper function.…”
Section: Resultsmentioning
confidence: 99%
“…CO 2 then diffuses across the thylakoid membrane to the proximate Rubisco active sites and is fixed into 3‐phosphoglycerate. LCIB/LCIC, which structurally resembles a carbonic anhydrase, localizes peripheral to the pyrenoid matrix and is hypothesized to function in recapture (hydration) of CO 2 leaking from the pyrenoid . Another prominent feature of the Chlamydomonas pyrenoid is a starch sheath that physically surrounds the compartment and is formed in response to low CO 2 concentrations .…”
Section: The Need For a Microalgal Rubisco Superchargermentioning
confidence: 99%
“…In a similar manner, the in vitro assay allows us to test whether completely unrelated control proteins or proteins known to be absent from the pyrenoid matrix (for instance, other Calvin cycle enzymes or the predicted carbonic anhydrase LCIB/LCIC) are actively excluded from the droplets or whether their in vivo localization will be determined by other mechanisms. Mackinder et al reported that proteins exceeding 78 kDa appear to be absent from the pyrenoid matrix, which could be caused by the surface tension of the liquid phase .…”
Section: A Molecular Dissection Of Pyrenoid Compositionmentioning
confidence: 99%
“…The other two Ci flux-associated proteins are CAH3, a thylakoid lumen-localized carbonic anhydrase; and LCIB found in the chloroplast stroma. Although the precise function of LCIB is unclear, LCIB orthologs in other algae function as carbonic anhydrases that are perhaps involved in CO 2 recapture by directional hydration of CO 2 to HCO 3 À (Jin et al, 2016;Kikutani et al, 2016). limiting CO 2 (Turkina et al, 2006;Blanco-Rivero et al, 2012;.…”
Section: Box 1 Proteins Unambiguously Involved In Inorganic Carbon (Cmentioning
confidence: 99%